Barriers to Diversification and Regional Allocation of Capital - Udo Broll; Antonio Roldán-Ponce; Jack E. Wahl (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
In order to evaluate the allocational effectiveness of regional policy when harmonizing regional economic conditions firms? preferences play a pivot role. If harmonization hinders risk diversification of the firm, then instead of regional diversification of capital agglomeration of capital occurs. Hence, regional policy will not achieve its objective to equal the spatial allocation of capital.
Keywords: R30; R12; R38; 330; Regional policy; agglomeration; diversification; allocation; risk aversion; prudence; Regionalpolitik; Allokationseffizienz; Investition; Risikoaversion; Regionale Konzentration; Regionale Disparitaẗ; Theorie